Factors affecting choice of employment by university graduates - Šnýdrová, Markéta; Vnoučková, Lucie; Šnýdrová, Ivana (Univerzita Pardubice, 2019)
The article focuses on factors influencing employer selection from the perspective of graduates of the University of Economics and Management. The aim of the article is to identify factors affecting attractiveness of organization and to determine the impact of these factors on the choice of employer in terms of the different focus of the applicants. Primary research included a questionnaire (n = 238 respondents), 4 focus groups and two individual interviews. The results of primary research have shown that the most important areas are: a prestigious and respected company, a purely Czech company, a stable established company with tradition, TOP employer, a socially responsible company, possibility of career growth, possibility of further development, the opportunity to participate in corporate goals, participation in decision making and management of the company, the possibility to apply creativity, innovation and ideas, individual work, interesting work, challenge work, ambitious project, financial remuneration, corporate benefits and geographic availability of the organization. The research also showed that preferences can be divided into factors that indicate whether an organization becomes a selected (attractive) employer based on the candidate's specific focus. Factor analysis has shown that different factors are important for identified types of candidates. The output of the article is a recommendation on what factors organization should focus on to address a particular type of candidate.
Keywords: employer attractiveness; factors influencing employer selection; organization; applicant; employee; university graduate; J20; M51